Towards an effective legal framework for online dispute resolution in e-commerce transactions: trends, traditions, and transitions - Omoola, Sodiq Olalekan; Oseni, Umar Aimhanosi (IIUM Press, International Islamic University Malaysia, 2016)
The need for convergence of best practices in Alternative Dispute Resolution (ADR) and Information and Communication Technology (ICT) cannot be overemphasised in an increasingly digitalised world. This undoubtedly led to the introduction of Online Dispute Resolution (ODR) few decades ago which is considered a fast, seamless, and convenient means of dispute resolution. With the increasing prominence of e-commerce transactions, several countries and regions of the world are on the quest to provide an effective legal framework for ODR in e-commerce dealings. This paper analyses the approaches to ODR legislations for consumer protection in selected jurisdictions. The paper finds that a comparative legal approach with some leverage on legal borrowing can help to create the required legal environment for ODR in other jurisdictions.